Serological evidence of avian encephalomyelitis virus infection associated with vertical transmission in chicks. Issue 6 (November 2015) - Yu, Xiao-hui; Zhao, Jing; Qin, Xiu-hui; Zhang, Guo-zhong
Abstract: Avian encephalomyelitis virus (AEV) can be transmitted both horizontally and vertically. In the present study, we report a typical case of AEV infection in broiler breeder chickens and their progeny identified by clinical survey of the disease, antibody detection, and reverse transcription (RT)-polymerase chain reaction (PCR) assay.